Diagnosis and Treatment of Childhood Pulmonary Tuberculosis: A Cross-Sectional Study of Practices among Paediatricians in Private Sector, Mumbai - Tauro, Carolyn Kavita; Gawde, Nilesh Chandrakant (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Majority of children with tuberculosis are treated in private sector in India with no available data on management practices. The study assessed diagnostic and treatment practices related to childhood pulmonary tuberculosis among paediatricians in Mumbai’s private sector in comparison with International Standards for Tuberculosis Care (ISTC) 2009. In this cross-sectional study, 64 paediatricians from private sector filled self-administered questionnaires. Cough was reported as a symptom of childhood TB by 77.8% of respondents. 38.1% request sputum smear or culture for diagnosis and fewer (32.8%) use it for patients positive on chest radiographs and 32.8% induce sputum for those unable to produce it. Sputum negative TB suspect is always tested with X-ray or tuberculin skin test. 61.4% prescribe regimen as recommended in ISTC and all monitor progress to treatment clinically. Drug-resistance at beginning of treatment is suspected for child in contact with a drug-resistant patient (67.7%) and with prior history of antitubercular treatment (12.9%). About half of them (48%) request drug-resistance test for rifampicin in case of nonresponse after two to three months of therapy and regimen prescribed by 41.7% for multidrug-resistant TB was as per ISTC. The study highlights inappropriate diagnostic and treatment practices for managing childhood pulmonary TB among paediatricians in private sector.